Diffusion tensor imaging of white matter degeneration in early stage of Alzheimer's disease: a review. (3rd March 2020) - Lo Buono, Viviana; Palmeri, Rosanna; Corallo, Francesco; Allone, Cettina; Pria, Deborah; Bramanti, Placido; Marino, Silvia
Abstract: Object: Alzheimer's disease is a progressive, irreversible neurodegenerative disorder associated with brain alterations. Diffusion tensor imaging (DTI) has contributed to identify degeneration in white matter cortical microstructural that can be considered an early and specific biomarker for Alzheimer's disease. This review aimed to provide a summary of DTI studies on white matter damage in Alzheimer's disease. Methods: On PubMed, Web of Science and Scopus databases, we reviewed the studies that used DTI for assessing fractional anisotropy in neurofiber tracts involved in Alzheimer's Disease progression: fornix, the cingulum, uncinate fasciculus, superior and inferior longitudinal fasciculus and corpus callosum. We included nine studies that met search criteria. Results: The results showed decreased fractional anisotropy value in mild cognitive impairment (MCI) patients. White matter diffusivity changes were associated with the progression of Alzheimer's disease. Conclusion: Microstructural alterations of the limbic and cortico-cortical tracts could be potential biomarkers for early diagnosis in preclinical disease phase.